Profit Balance, Stock Trading Volume, Return On Investment And Stock Prices - Ardian Prima Putra; Pristin Prima Sari; Harmadi Harmadi (UNIVED Press, 2025)
The purpose of the research is to empirically test the profit balance of stock prices, stock trading volume and return on invested capital (ROI). This research method used quantitative linear regression analysis using SPSS IBM 20. The information comes from the quarterly financial reports listed in the Indonesian Stock Exchange for the years 2018-2020. The results of the F-test show that the earnings ratio, stock market trading volume and return on invested capital (ROI) have a significant impact on stock prices. At the same time, the t-test shows that profit balance, stock trading volume and return on invested capital (ROI) partially significantly affect stock prices.